Primary amenorrhoea due to ovarian dysgenesis: a previously undescribed chromosome 12 abnormality. (11th January 2011) - Grant, Paul; Lipscomb, David
Abstract : This case describes for the first time a de novo chromosomal abnormality (46, XX, inv dup del(12)(qter-p13.3::p13.3-p12.3:)dn.ish inv dup del(12)(TEL-ETV6++) which produced the phenotype of a female with primary ovarian failure and subsequent osteopenia in early adult life. This warranted treatment with oestrogen replacement therapy and close supportive monitoring.